Effectiveness of Using Timeline Media Based on Focusky Applications to Improve Chronological Thinking Skills - Marni Emiar Pratiwi; Ofianto Ofianto (Postgraduate School, Universitas Negeri Padang, 2022)
Chronological thinking skill is very important in history learning to maximize the achievement of learning. This study aims to develop learning media designed to support the improvement of chronological thinking skills in the form of timeline media. This type of research is experimental students from two schools, namely two classes from SMAN and one class at MAN. The data of this research are in the form of quantitative data, namely data obtained from the feasibility and practicality questionnaire as well as the effectiveness test result sheet. This research produces a media timeline that is feasible and practical to use as a medium in history learning and can improve students' chronological thinking skills in the process of learning Indonesian history at the SMA/MA level.